2014
DOI: 10.1016/j.pain.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential upregulation in DRG neurons of an α2δ-1 splice variant with a lower affinity for gabapentin after peripheral sensory nerve injury

Abstract: SummaryA minor α2δ-1 splice-variant, (ΔA+BΔC), with reduced affinity for gabapentin, is differentially upregulated in DRG neurons following ligation. This could influence the efficacy of gabapentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…In our studies, a marked increase in gabapentin binding affinity was observed for both a 2 d-1 and a 2 d-2 purified in detergent-resistant membrane (lipid raft) fractions compared with total membrane fractions Lana et al, 2014). For example, the binding of 3 H-gabapentin to a 2 d from membranes from mouse cerebellum (predominantly a 2 d-2, which is strongly expressed in Purkinje neurons) gave a K D of approximately 385 nM, whereas the K D was approximately 80 nM in detergent-resistant membranes from the same tissue .…”
supporting
confidence: 49%
See 3 more Smart Citations
“…In our studies, a marked increase in gabapentin binding affinity was observed for both a 2 d-1 and a 2 d-2 purified in detergent-resistant membrane (lipid raft) fractions compared with total membrane fractions Lana et al, 2014). For example, the binding of 3 H-gabapentin to a 2 d from membranes from mouse cerebellum (predominantly a 2 d-2, which is strongly expressed in Purkinje neurons) gave a K D of approximately 385 nM, whereas the K D was approximately 80 nM in detergent-resistant membranes from the same tissue .…”
supporting
confidence: 49%
“…A change in a 2 d-1 splicing was recently found in rat DRG neurons, after spinal nerve ligation. Increased expression was observed of a minor splice variant (DA + BDC), particularly in small DRG neurons, and this showed a lower affinity for gabapentin (Lana et al, 2014). There are also splice variants of the other a 2 d subunits, but their expression has not been studied in detail (Klugbauer et al, 1999;Barclay and Rees, 2000;Qin et al, 2002).…”
Section: A a 2 D Subunit Genes And Gene Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility relates to differences in the properties of ␣2␦-subunits in the different neuron types. This is supported by the recent description of two splice variants of the ␣2␦-1 subunits in DRG neurons (Lana et al 2013). One, designated ␣2␦-1 ⌬AϩBϩC, is found in many brain regions, whereas the other, ␣2␦-1 ⌬AϩB⌬C, is upregulated in small DRG neurons following nerve injury.…”
Section: Discussionmentioning
confidence: 62%